Voltage stability control method of electric springs based on adaptive PI controller. (February 2018) - Ma, Gang; Xu, Guchao; Chen, Yixi; Ju, Rong
Highlights: An adaptive PI controller is proposed to improve the performance of the electric springs. Advanced PSO algorithm and fuzzy control are used in PI controller. The changes of non-critical load are considered during electric springs' operation. The approach is verified through simulation analysis and comparative studies with traditional PI control. Abstract: With the continuous development of distributed generation technology, the permeability of wind, solar and other renewable energy continues to increase. As a new kind of voltage control device, electric spring can suppress the voltage fluctuation caused by the power change of distributed generation effectively. In this paper, based on the analysis of the principle of voltage stability control for the electric spring, the optimization of control effect and non-critical load change are taken into consideration. Combined with advanced particle swarm optimization algorithm and fuzzy control algorithm, a method of voltage control for electric spring based on adaptive PI control is proposed, and the digital simulation is carried out. The simulation results show that the adaptive PI control has better voltage regulation effect than the traditional PI control, and can solve the adverse effect of the load variation on the electric spring.